A cartografia digital das escolas rurais do campo como dispositivo na formação continuada de professores - Rechia, Marijane (2019)
This dissertation, entitled Digital Cartography of Rural Schools in the Field as a Device in the Continuing Education of Teachers, has as its origin the investigations carried out in the Research Project “Cartography of Basic Education in Rural Schools: perspectives for the formation and performance of teachers of central region of Rio Grande do Sul - CEBER and is linked to the Research Line Training, Knowledge and Professional Development”, produced in the Graduate Program in Education of the Federal University of Santa Maria - UFSM. In this sense, it has as its main objective understand how digital cartography can enhance teacher education, communication, and relationships between rural schools in the field of the 8th Regional Education Coordination (CRE). Anchored in a qualitative approach, in the modality of case study, this research had as the production of information, the results of interviews, narratives that were carried out with the literacy teachers of two of the thirty rural state schools in the field that participated of the CEBER project. The theoretical framework is based on Antunes (2001, 2007); Freire (1996); Josso (2007); Maciel (2006); Fog (1995, 2009); Ribas and Antunes (2014); (2007); Souza (2005), Souza and Antunes (2017), Tardif (2002, 2005) among others. This research deals with the development of a Digital Cartography, as a potentializing project, to enable the exchange of information and continuing education for teachers of rural schools in the countryside, as well as for other researchers. With the intention of answering how this digital cartography can be a potentializing tool in the continuous formation of teachers, in the communication and the relations between rural schools of the 8th CRE field, I realize that the development of this research may help in the perception of the importance of providing the exchange of knowledge, shared and cooperative work among teachers, as well as encouraging the appreciation of belonging to the place of origin and the context of professional practice. I conclude that such digital cartography is a potentializing tool because it allows teachers to search for information, share experiences, exchange knowledge and strengthen the teaching profession. Due to its importance, it is necessary to continue this research, its dissemination, and the continuous in-service training to expand its use.